2011
DOI: 10.2478/v10172-011-0107-8
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Friction Coefficient in Friction Welding Process of Tubular Steel Elements

Abstract: The paper presents a research on the relationship between friction coefficient and friction pressure (6 MPa, 12 MPa, 16.5 MPa), rotational speed (1000 rpm, 1400 rpm, 2000 rpm) and surface temperature during traditional friction welding. Values of friction pressure force and friction torque were read on an oscilloscope connected to a piezoelectric sensor and temperature was measured with a thermovision camera on circumference of the welding surface and in the heat-affected zone. Friction was measured between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Where M < refers to the friction torque in Nm, P < is the pressure force in N and r is the radius of the cylindrical welded specimen, considered as 8 mm in the study [34]. It was concluded that the friction coefficient was maximised in the low temperature range and was stabilised at 0.3 after reaching above 400°C.…”
Section: Boundary Conditionsmentioning
confidence: 98%
See 3 more Smart Citations
“…Where M < refers to the friction torque in Nm, P < is the pressure force in N and r is the radius of the cylindrical welded specimen, considered as 8 mm in the study [34]. It was concluded that the friction coefficient was maximised in the low temperature range and was stabilised at 0.3 after reaching above 400°C.…”
Section: Boundary Conditionsmentioning
confidence: 98%
“…The coefficient of friction is a significant component in calculating the heat generation between two surfaces. Different researchers have estimated different values for different material interactions under specific conditions [33,34]. Nandan et al [33] computed the friction coefficient by considering the relative velocity between rotating tool and workpiece and used a value of 0.4.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…All model settings were replicated from the model FSW -1, also referred as the fast weld model in the previous research [26]. The entire workpiece was assigned a fixed initial temperature of 25 o C. A frictional coefficient of 0.3 was used to provide a feasible contact property definition between all surfaces, as discussed in previous studies [26,31]. To transfer the heat from workpiece to the surrounding, convective coefficients of 10 and 2000 W/m 2 K were applied on the top/sides and bottom surfaces of the workpiece, respectively.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%